2003
DOI: 10.1046/j.1095-8339.2003.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenesis variation in the Turnera sidoides L. polyploid complex (Turneraceae)

Abstract: This study constitutes the first investigation of cyanogenesis variation within the Turnera sidoides autopolyploid complex. The qualitative and quantitative analysis carried out in 38 populations showed that the five subspecies of the complex are cyanogenic, although the levels of cyanide released varied both between and within subspecies. Between the subspecies, carnea, holosericea and integrifolia showed higher values of HCN released than subspecies pinnatifida and sidoides. Within subspecies, there is a ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…However, Manihot esculenta (McMahon et al . 1995), Eucalyptus yarraensis ( n = 170; Goodger & Woodrow 2002) and the Turnera sidoides species complex ( n > 190; Solís Neffa et al . 2003) are also known for their complete absence of acyanogenic individuals and recent work by Miller et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Manihot esculenta (McMahon et al . 1995), Eucalyptus yarraensis ( n = 170; Goodger & Woodrow 2002) and the Turnera sidoides species complex ( n > 190; Solís Neffa et al . 2003) are also known for their complete absence of acyanogenic individuals and recent work by Miller et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hughes 1991;Schappert & Shore 1995). However, Manihot esculenta (McMahon et al 1995), Eucalyptus yarraensis (n = 170; Goodger & Woodrow 2002) and the Turnera sidoides species complex (n > 190;Solís Neffa et al 2003) are also known for their complete absence of acyanogenic individuals and recent work by Miller et al (2004Miller et al ( , 2006 has found that a number of other Australian rain forest trees appears to be uniformly cyanogenic. It may be that the high herbivore pressures in rain forest ecosystems, relative to temperate environments (Coley & Barone 1996), have selected against acyanogenic phenotypes in cyanogenic rain forest species.…”
Section: P O P U L a T I O N -Level C Y A N O G E N E S I Smentioning
confidence: 99%
“…The majority of plant species where reasonable numbers of individuals have been tested have reported a certain percentage of functionally acyanogenic individuals (e.g. Cooper-Driver and Swain, 1976;Ellis et al, 1977;Dirzo and Harper, 1982;Till, 1987;Hughes, 1991;Schappert and Shore, 1995;Aikman et al, 1996;Pederson et al, 1996;Bazin et al, 1997;Goodger et al, 2002;Gleadow et al, 2003; but see Kakes, 1994;McMahon et al, 1995;Solís Neffa et al, 2003). Locating and testing larger populations of the rare R. kurrangii will be required to confirm if this species has qualitative as well as quantitative polymorphism for cyanogenesis.…”
Section: Population Cyanogenesis Studiesmentioning
confidence: 96%
“…38621, 38695 y 38754 (Fernández, 1987). Cariotipo: Krapovickas & Schinini 36653 (Solís Neffa, 1996). Distribución: Especie de amplia distribución en el centro y Este de Brasil (Alagoas, Amapá, Amazonas, Bahia, Ceará, Goiás, Maranhão, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Pará, Paraíba, Pernambuco, Piauí, Rio Grande do Norte, Rondonia y Tocantins) norte y este de Bolivia y noreste de Paraguay.…”
Section: Turnera Luetzelburgii Sleumerunclassified
“…La variación en la subsp. pinnatifida podría estar relacionada con la presión de selección ejercida por diferentes regímenes climáticos (Solís Neffa & al. 2003).…”
Section: Turnera Rosulataunclassified